Investigating the Impact of Sustainable Procurement on Economic Growth and Development - Bugri, Benjamin Adelwini; Michael, Appiah; Arthur, Emmanuel Awusi (Journal of Accounting, Business and Finance Research, 2019)
The usage of public procurement to accomplish economic growth and development is extensive, but through evidence about its operations are often imprecise and challenging to discover. This study in effect is to look at the impact and linkage between sustainable procurement and economic growth in Ghana from 1975-2015. The article considers the Solow-Swan growth model and came out with the findings and a result that is consistent with most studies. It was realized that there is a positive and strong relationship as well as the significant impact between sustainable procurement and economic growth. Also, it was recorded that trade openness can be a catalyst for economic growth and development as the results proved there is a significant impact. A Johansen cointegration was employed to determine the long run relationship between economic growth and sustainable procurement and it was found out that there exists a long run relationship. Vector Error Correction Model was employed to study the long run and short run impact of sustainable procurement on economic growth. The study also came out that recently, procurement is employed as a tool to promote economic growth as well as attain sustainable development goals. The study contains some reflections on the connections between procurement and economy, society and environment.